Transcutaneous Electrical Nerve Stimulation in Patients With Knee Osteoarthritis: Evidence From Randomized-controlled Trials. Issue 2 (February 2016) - Chen, Ling-Xiao; Zhou, Zhi-Rui; Li, Yu-Lin; Ning, Guang-Zhi; Li, Yan; Wang, Xiao-Bo; Feng, Shi-Qing
Abstract : Objectives: Transcutaneous electrical nerve stimulation (TENS) has been reported to relieve pain and improve function in patients with knee osteoarthritis. The purpose of this systematic review and meta-analysis was to evaluate the efficacy of TENS for the management of knee osteoarthritis. Methods: We searched Embase, PubMed, CENTRAL, SIGLE, PEDro, and clinicaltrials.gov, up to June 2014 for literature related to TENS used for the treatment of knee osteoarthritis. Two authors independently screened the searched records based on the title and abstract. Information including the authors, study design, mean age, sex, study population, stimulation frequency (of TENS), outcome measures, and follow-up periods were extracted by the 2 authors. Results: Eighteen trials were included in the qualitative systematic review, and 14 were included in the meta-analysis. TENS significantly decreased pain (standard mean difference, −0.79; 95% confidence interval [CI], −1.31 to −0.27; P <0.00001) compared with control groups. There was no significant difference in the Western Ontario and McMaster Universities Osteoarthritis Index (standard mean differences, −0.13; 95% CI, −0.35 to 0.1; P =0.09) or the rate of all-cause discontinuation (risk ratio, 0.77; 95% CI, 0.48 to 1.22; P =0.94) between the TENS and control groups. Discussion: TENS might relieve pain due to knee osteoarthritis. Further randomized-controlled trials should focus on large-scale studies and a longer duration of follow-up. Abstract : Supplemental Digital Content is available in the text.